The Role of AI in Personalized Learning: Enhancing Creative Thinking in Online Classrooms - Loso Judijanto; Ammar Al-Momani; Siti Aisyah Hanim; Ardi Azhar Nampira (Yayasan Adra Karima Hubbi, 2025)
The rapid integration of Artificial Intelligence (AI) into education has transformed the dynamics of online learning, creating opportunities for personalized learning pathways. However, the potential of AI to enhance creative thinking skills among students remains underexplored. This study aims to investigate the role of AI-driven personalized learning systems in fostering creative thinking in online classrooms. A quantitative research design with a quasi-experimental approach was applied, involving 240 university students enrolled in fully online courses. The experimental group used AI-powered adaptive learning platforms, while the control group participated in conventional online learning. Data were collected through creative thinking tests and analyzed using ANCOVA to measure the impact of the intervention. The findings indicate that AI-based personalization significantly improves students’ creative thinking, particularly in generating novel ideas, problem-solving flexibility, and originality of responses. The study concludes that AI can serve as an effective catalyst for promoting creativity in digital learning environments by tailoring content, pace, and feedback to individual learners. This research provides evidence for integrating AI tools in designing student-centered online learning models that emphasize creativity as a 21st-century skill.